2009
DOI: 10.1073/pnas.0807485106
|View full text |Cite
|
Sign up to set email alerts
|

The Rap80-BRCC36 de-ubiquitinating enzyme complex antagonizes RNF8-Ubc13-dependent ubiquitination events at DNA double strand breaks

Abstract: DNA double strand breaks (DSBs) initiate reversible cellular checkpoint and repair activities. Whereas many of the activating events at DSBs have recently been elucidated, the mechanisms used to terminate responses at these sites are largely undefined. Here we report a pathway required to reverse RNF8-Ubc13 dependent ubiquitination events on chromatin flanking DSBs. Inhibition of the Rap80-BRCC36 de-ubiquitinating enzyme complex partially restored DSB-associated ubiquitin levels following RNF8 knockdown or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
207
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(215 citation statements)
references
References 36 publications
7
207
0
Order By: Relevance
“…Depletion of BRCC36 compromised the G 2 /M cell cycle checkpoint, impaired BRCA1 recruitment onto DSBs, resulted in hyperactive homologous recombination (HR)-based gene conversion events and hypersensitized the cell to genotoxic stress (7)(8)(9)(10)(11)(12). Consistent with the idea that dysregulated DNA repair promotes tumorigenesis, aberrant expression of BRCC36 has been associated with breast carcinomas (19) and nasopharyngeal carcinomas (20) and represents a promising prognostic marker and a potential target in the therapies for these cancer types.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Depletion of BRCC36 compromised the G 2 /M cell cycle checkpoint, impaired BRCA1 recruitment onto DSBs, resulted in hyperactive homologous recombination (HR)-based gene conversion events and hypersensitized the cell to genotoxic stress (7)(8)(9)(10)(11)(12). Consistent with the idea that dysregulated DNA repair promotes tumorigenesis, aberrant expression of BRCC36 has been associated with breast carcinomas (19) and nasopharyngeal carcinomas (20) and represents a promising prognostic marker and a potential target in the therapies for these cancer types.…”
mentioning
confidence: 52%
“…Indeed, BRCC36 resides within the BRCA1-A macromolecular protein complex, which comprises the ubiquitin-binding protein RAP80, BRCC45/BRE, Abraxas/CCDC98, Merit40/NBA1, and BRCA1. The BRCA1-A complex is targeted to chromatin domains surrounding DNA double strand breaks (DSBs) by the ubiquitin-binding protein RAP80, which preferentially binds to K63-Ub adducts generated by the ubiquitin-conjugating enzyme UBC13 (3,(7)(8)(9)(10)(11)(12). Abraxas plays a major scaffolding role to support the integrity of the BRCA1-A assembly and directly anchors the tumor suppressor BRCA1 via a phosphorylation-dependent interaction (13)(14)(15).…”
mentioning
confidence: 99%
“…NBA1 deficiency leads to decreased levels of Abraxas, BRE, and BRCC36 (16,17,20). In this study, we found that NBA1 and BRE interaction plays an important role in maintaining the integrity of both of the BRCC36-containing complexes.…”
mentioning
confidence: 55%
“…The activity of POH1 is enigmatic. Based on in vitro enzymatic and structural studies of AMSH, BRCC3, and POH1, it has been proposed that the JAMM family proteins may collectively possess a stringent specificity for Lys63 ubiquitin chain linkages (44,45,123,171,225,235). However, elegant preceding work suggested that POH1 activity on proteasomal substrates 1) indirectly requires ATPase activity presumably for unfolding of the substrate, 2) is coupled to proteasomal degradation, and 3) completely removes ubiquitin by cleavage at the base of the ubiquitin chain (266,284).…”
Section: A Proteasomal Dubsmentioning
confidence: 99%